Isolation and identification of amylolytic bacteria from ragi - Roslan R.; Kamarudin K.R.; Maryam Mohamed Rehan; Hanina Mohd Noor; Nur Huda Faujan; Salina Mat Radzi (Malaysian Society of Applied Biology, 2024)
Indexed by SCOPUS